Tender Morsels - Lanagan, Margo (Random House Group Ltd)
Tender Morsels is a dark and vivid story, set in two worlds and worrying at the border between them. It is a gloriously told tale of journeys and transformations, penetrating the boundaries between male and female, reality and myth, conscious and unconscious, temporal and spiritual, human and beast.
Keywords: Fantasy; Fiction; Juvenile Literature